Challenges And Strategy for Achieving Academic Well-Being Among KIP-K Scholarship Recipients: A Qualitative Study - Sandy Chandra Jesmen Malaikosa; Arthur Huwae (Universitas PGRI Yogyakarta, 2026)
Financially disadvantaged students can receive assistance from the KIP-K scholarship program to continue their education at a university. However, during the lecture process, students participating in the KIP-K program experience academic and psychosocial challenges that impact their academic well-being. The purpose of this study is to describe the academic well-being of students receiving the KIP-K program. This study used a qualitative method with a descriptive phenomenological approach. The research participants were 10 students who received the KIP-K program using a purposive sampling technique. Data were collected through semi-structured interview techniques to gain an understanding of academic well-being. The results showed that students who received the KIP-K program experienced academic well-being through different processes. KIP-K recipients face challenges such as financial constraints, academic burnout, and learning difficulties, but develop resilience through motivational strategies, time management, and social support. Keywords: academic well-being, university students, KIP-K scholarship program